2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24872
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped Classroom: It's (Still) All About Engagement

Abstract: Our collective experience in comparing the results of teaching three courses using a variety of flipped classroom formats and the traditional format showed no compelling improvement of student learning results using the flipped format. Specifically, comparison of student outcomes in the form of grades does not show a consistent difference between a flipped classroom environment and a traditional teaching environment.The results we observed have made us aware of the need to be more systematic in the pedagogy pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…13 However, Roa, Collins, and DiCarlo find "completing the quizzes in groups enhances the understanding of the material." 14 Moreover, Leight et al hypothesis that collaborative testing might improve students' obtainment of lowerorder learning outcomes (Bloom's levels 1 and 2), but not higher-order learning outcomes (Bloom's levels [3][4][5][6]. 15 Background Informal collaboration has always been encouraged in the two inverted courses of the present study: Thermodynamics and Mechanical Engineering Analysis.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…13 However, Roa, Collins, and DiCarlo find "completing the quizzes in groups enhances the understanding of the material." 14 Moreover, Leight et al hypothesis that collaborative testing might improve students' obtainment of lowerorder learning outcomes (Bloom's levels 1 and 2), but not higher-order learning outcomes (Bloom's levels [3][4][5][6]. 15 Background Informal collaboration has always been encouraged in the two inverted courses of the present study: Thermodynamics and Mechanical Engineering Analysis.…”
Section: Introductionmentioning
confidence: 94%
“…However, several recent studies provide evidence that, when compared with other active learning pedagogies, the flipped classroom itself does not improve students' performance on traditional classroom assessments or design activities. [2][3][4][5][6][7][8][9][10] However, as one of the authors writes in a recent ASEE paper 11 there may be other reasons beyond students' immediate content learning to utilize the flipped classroom. One of these other reasons to flip a class is to implement structured student collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…Mason also reported, however, that students in the same course reported doubts about freshmen and sophomore students possessing the maturity needed to succeed in the flipped format. Prust et al 10 reported student enthusiasm for the flipped model but few tangible gains in performance. They hypothesize this is due to a lack of student engagement with the required materials outside of class.…”
Section: Introductionmentioning
confidence: 99%
“…The flipped classroom approach has increased in popularity for engineering and science courses [1] [2] in part because the traditional lecture approach is perceived to be ineffective for teaching essential problem-solving skills [3] . Time spent in the classroom is thought to be better used when the instructor supports students working in groups on problem-solving and other active learning activities.…”
Section: Introductionmentioning
confidence: 99%
“…In most flipped classroom implementations, the course content is presented through video lessons accessed online and which are either prepared by the course instructors or curated from existing sources [2] . The flipped classroom approach does not prescribe to include in the online content means for the students to test their knowledge and understanding.…”
Section: Introductionmentioning
confidence: 99%